Kaukaz w ostatnim roku życia i twórczości Michaiła Lermontowa - Jatczak, Grażyna (Studia Rossica Posnaniensia, 2012)
The theme of Caucasia is present in all of Lermontov’s works. In the last year of his life the poet altered the way Caucasia and its inhabitants were perceived. He changed this from a romantic to a realistic description and began the process of deglorifying his characters, as he was interested in the Eastern mentality and philosophy.